Pengaruh Pemeberian Ekstrak Etanol Delphinium Grandiﬂ orum Terhadap Tanda Somatik dan Tanda Afektif Nicotine Withdrawal Syndrome pada Tikus Sprague Dawley Betina yang Diberi Nikotin Peroral - Nurvita Risdiana (IJNP (Indonesian Journal of Nursing Practices), 2014)
Background. Nicotine abstinence will lead nicotine withdrawal syndrome in somatic signs and aﬀ  ective signs. Somatic signs such as body weight change. Aﬀ  ective signs such as sign of anxiety. Nicotine withdrawal syndrome will increasing the desire to use nicotine. Delphinium grandiﬂ orum is a plant with methyllcyaconitine (MLA). Methyllcyaconitine (MLA) is antagonist competitive which block α7 nAChRs. It will lowering the desire to use nicotine without induce nicotine withdrawal syndrome. Objective. To know the eﬀ  ect of ethanolic extract Delphinium grandiﬂ orum in somatic signs and aﬀ  ective signs of nicotine withdrawal syndrome in Sprague Dawley female rats treated with oral nicotine.Methods. This study was quasi experiment with pre and post control group design. Rats were grouped into 4 groups. The groups are OO (control), NO (nicotine+aquabides), ND 3 (nicotine+ D. grandiﬂ orum 3 mg/kg), ND 6 (nicotine+ D. grandiﬂ orum 6 mg/kg). Nicotine was given ad libitum. Nicotine was given via drinking water with a step wise increase of dosage every 4 days until 15 days. Somatic signs and aﬀ  ective signs were observed during 24 hours period after abstinentia (16th and 20th days) on dark cycle. Light cycle on 18.00- 06.00, dark cycle on 06.00-18.00. Aﬀ  ective signs was observed with open spent time and open arm entries by Elevated Plus Maze.Result. There is no signiﬁ cant diﬀ  erences between group for  body weight, open spent time and open arm entries on day 16 and 20. Conclution. There is have no eﬀ  ect of ethanolic extract Delphinium grandiﬂ orum and nicotine administration for somatic signs, aﬀ  ective signs of nicotine withdrawal syndrome in Sprague dawley female rats.Keywords. Nicotine, nicotine withdrawal syndrome, somatic signs, aﬀ  ective signs.